A clinical prediction model for distant metastases of pediatric neuroblastoma: an analysis based on the SEER database - Yan, Zhiwei; Wu, Yumeng; Chen, Yuehua; Xu, Jian; Zhang, Xiubing; Yin, Qiyou (Frontiers in Pediatrics, 2024)
Background: Patients with distant metastases from neuroblastoma (NB) usually have a poorer prognosis, and early diagnosis is essential to prevent distant metastases. The aim was to develop a machine-learning model for predicting the risk of distant metastasis in patients with neuroblastoma to aid clinical diagnosis and treatment decisionsWe built a predictive model using data from the Surveillance, Epidemiology, and End Results (SEER) database from 2010-2018 on 1,542 patients with neuroblastoma. Seven machinelearning methods were employed to forecast the likelihood of neuroblastoma distant metastases.Univariate and multivariate logistic regression analyses were used to identify independent risk factors for building machine learning models.. Secondly, the subject operating characteristic area under the curve (AUC), Precision-Recall (PR) curves, decision curve analysis (DCA), and calibration curves were used to assess model performance. To further explain the optimal model, the Shapley summation interpretation method (SHAP) was applied. Ultimately, the best model was used to create an online calculator that estimates the likelihood of neuroblastoma distant metastases.The study included 1,542 patients with neuroblastoma, multifactorial logistic regression analysis showed that age, histology, tumor size, tumor grade, primary site, surgery, chemotherapy, and radiotherapy were independent risk factors for distant metastasis of neuroblastoma (P < 0.05).Logistic regression (LR) was found to be the optimal algorithm among the seven constructed, with the highest AUC values of 0.835 and 0.850 in the training and validation sets, respectively.. Finally, we used the logistic regression model to build a network calculator for distant metastasis of neuroblastoma.The study developed and validated a machine learning model based on clinical and pathological information for predicting the risk of distant metastasis in patients with neuroblastoma, which may help physicians make clinical decisions.